Matrimonial Politics in Thirteenth-Century Aragon: Moncada v. Urgel - Brundage, J. A. (The journal of ecclesiastical history, 1980)
Since apostolic times Christians have treated the family as a micro-community which reflects the values and problems of the larger Christian community as a whole. Most communities, including Christian ones, are reluctant to contemplate the possibility that their own existence will end. But although Jesus is said to have promised St Peter that His Church would survive death, and although the notion of the Church as a community that never dies became a commonplace in subsequent ecclesiology, there was no such guarantee of immortality to the individual family. The breakup and restructuring of family units through death or the dissolution of marriage was a reality which medieval Christian communities had to face in each generation. Even so, high-ranking social groups sought to minimise generational disruptions by adopting the fiction of the family that never dies, a notion that is especially familiar to historians of the theory of monarchy in the Middle Ages. The medieval Church was a keen champion of the continuity of domestic units. As Georges Duby has recently pointed out, the Church in the early Middle Ages struggled mightily to make its own theory of marriage prevail over the alternative marriage theory popular among the laity. The ecclesiastical model of marriage, which emphasised the free consent of the contracting parties and the indissolubility of unions, triumphed over the lay model of marriage, which, according to Duby, valued family concerns above the wishes of the individual at the end of the eleventh century in France. The pattern of marriage arrangements that Duby calls the lay model seems to have persisted vigorously until much later in other places, including Catalonia and Aragon. This paper will examine a case from mid-thirteenth century Arago-Catalonia in which the conflict of lay and ecclesiastical marriage ideals features prominently.